Design of a 3600 Virtual Reality Website for the Department of Electrical Engineering Sriwijaya State Polytechnic - Iqbal, Muhammad; Taqwa, Ahmad; Lindawati, Lindawati (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Information technology plays a crucial role in meeting the aspirations of people seeking knowledge in higher education institutions. One effective strategy to showcase the unique features of each university is by employing a Virtual Reality Website 3600. Through this Virtual Reality Website, prospective students, visitors, and the general public can experience a more immersive understanding of the facilities and lecture rooms in the Department of Electrical Engineering at Sriwijaya State Polytechnic (POLSRI). Users can feel as if they are physically present and interact with the college environment virtually using the 3600 camera technology. In this research, to ensure the security of user data and prevent potential security threats, a One-Time Password (OTP) security mechanism is implemented on the website. The OTP system provides temporary access with unique codes generated each time a user accesses the website. This measure is taken to safeguard user data from unauthorized access and potential information leaks. The outcomes of this study will contribute to introducing users to the Virtual Reality Website 3600 technology and aid the Department of Electrical Engineering at POLSRI in virtually showcasing their facilities and lecture rooms to prospective students in an engaging manner.